The Development of Mobile Application of Organ Donation Using Flutter - Ong, Kai Sian; Suparjoh, Suriawati (Applied Information Technology And Computer Science, 2023)
In Malaysia, people require to visit government hospitals or health clinics and manually fill out the organ donation registration form to request to become an organ donor. However, the current manual registration process is time-consuming and difficult as on the way to the hospital, people will face traffic problems and need to wait in line for a long time. Therefore, a mobile application named “Pledge For Life” was developed by incorporating 2D animation to convey the information attractively. The methodology applied in this project is the prototyping model, which can determine the requirements in detail along the development process until achieving an acceptable outcome. The developed mobile application can assist people in registering to become organ donors and explore the information about organ donation in a better visualization with 2D animation. The User Acceptance Test (TAM) shows that 77.17% (Grade C) is within an acceptable result.